Application of Silver Compounds in Water Treatment and Prevention of Biofilm Formation in Water Distribution Channels - N B., Erena; N K., Mu’azu; M., Musah (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
Biofilm is a complex aggregation of microorganisms growing on a solid substrate (surfaces). Bacterial biofilms cause very serious problems in industrial water systems. This paper revealed biofilm as an aggregation of microorganisms that grows on solid surfaces or substrates. The surface can be living (body of animals and plants) or non-living (rocks and water pipes), they are characterized by structural interactions and cellular matrix of polymer substances which may be specific or non-specific. Biofilms affect many parts of everyday life, which include contamination of water, blocking of water channels and causing infections. Biofilm can be prevented by adequate cleaning of water storage systems and the use of antimicrobial agents also known as disinfectants. The paper also highlights notable disinfectants such as silver compounds, which when impregnated into water filters, robbins devices, diffusion gel and coatings of the inner surface of water channels can inhibit a lot of cellular activity of the microorganism and can also kill the organism. Silver and its compounds or in combination with other substances are used in the disinfection of water bodies for drinking and recreational activities. Silver and copper are the best antibiofilm agents. Robbins device with polyvinyl chloride and stainless steel surface used with 100µg/litre of silver compound is found to be effective in preventing biofilm formation. The paper concluded by recommending the use of silver compounds in water treatment and the prevention of biofilm formation in water channels. Due to the antimicrobial affinity of silver and its compounds, it has become one the best antibacterial agents in use today, for the prevention of biofilms in water channels, storage tanks and swimming pools, and also for domestic and municipal water treatment.